Is the I-131 whole-body scanning proper for follow-up management of patients with malignant struma ovarii without performing thyroidectomy? - Balci, TA; Kabasakal, L (Academic Press Inc Elsevier Science, 2005)
[Abstract Not Available]
Keywords: Cancer; Focus